Cadaveric Study of Anatomical Variations in the Musculocutaneous Nerve and in the Median Nerve - Priya, Abhilasha; Gupta, Chandni; D'souza, Antony Sylvan (Journal of Morphological Sciences, 2019)
Introduction The musculocutaneous nerve and the median nerve are branches from the lateral cord of the brachial plexus with a root value of C5, C6, and C7. The medial root of the median nerve is a branch of the medial cord. The present study aims at observing any variations in these peripheral nerves, so that this knowledge can be utilized by surgeons, anesthesiologists, and orthopedicians during surgical procedures and nerve block.Materials and Methods The present study was carried on 30 adult embalmed cadavers (60 upper limbs) in the department of anatomy of the Kasturba Medical College , Manipal, India. The infraclavicular part of the brachial plexus was dissected, and any anatomical variations in the formation and in the branching pattern of the musculocutaneous nerve and of the median nerve were noted and photographs were taken.Results The median nerve was noted to be formed from 3 roots in 8 out of 60 dissected upper limbs (13.33%). The musculocutaneous nerve was absent in 5% of the dissected limbs, and communications between these 2 nerves were noted in 13.33% of the dissected limbs.Conclusions Noted variations of the nerves may be of help to surgeons operating in the axillas and in the arms.
Keywords: communication; lateral cord; macroscopic human anatomy; median nerve; musculocutaneous nerve